Anno's Counting book - Anno, Mitsumasa, 1926- (New York : HarperCollins, 1977)
Introduces counting and number systems by showing mathematical relationships in nature.
Book Links (A.L.A.).
Elem. School Library Collection.
Wilson's Children.
K-3
Keywords: Counting -- Juvenile literature; Numeration -- Juvenile literature; Counting; Number systems; Counting; Numbers